The Longitudinal Effects of Early Language Intervention on Children's Problem Behaviors. Issue 2 (5th September 2017) - Curtis, Philip R.; Kaiser, Ann P.; Estabrook, Ryne; Roberts, Megan Y.
Abstract : Researchers examined whether a parent‐implemented language intervention improved problem behaviors 1 year after intervention. Ninety‐seven children with language delays (mean age at 12‐month follow‐up = 48.22 months) were randomized to receive Enhanced Milieu Teaching (EMT) language intervention or business as usual treatment. Twelve months after the intervention ended, children in the EMT intervention condition displayed lower rates of parent‐reported externalizing, internalizing, and total problem behaviors. A mediation analysis revealed that the relation between EMT and problem behaviors was partially mediated by child rate of communication for both internalizing and total problem behaviors. A developmental framework is proposed to explain the impact of EMT on problem behaviors, and future lines of research are discussed.